2004
DOI: 10.1007/s00216-003-2451-7
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of humic substances: Implications for trihalomethane formation

Abstract: Humic substances are precursors of carcinogenic trihalomethanes (THMs) formed during disinfection by chlorination in water treatment processes. In an effort to understand the relationship between trihalomethane formation potential (THMFP) and physicochemical properties of humic substances, UV-visible absorbance, fluorescence in emission and synchronous scan modes, and NMR spectra were measured for several aquatic fulvic and humic acids. For comparison, a soil fulvic acid was also examined using these methods. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 30 publications
0
28
0
1
Order By: Relevance
“…The ratio E 4 /E 6 is often used to describe the extent of condensation of the aromatic C-containing structures; low ratios reflect high degrees of condensation of aromatics, while high ratios mean the presence of large quantities of aliphatic structures and low amounts of condensed aromatics (Chin et al, 1997). This ratio is also inversely related to the degree of aromaticity, particle size, molecular weight and acidity (Uyguner et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…The ratio E 4 /E 6 is often used to describe the extent of condensation of the aromatic C-containing structures; low ratios reflect high degrees of condensation of aromatics, while high ratios mean the presence of large quantities of aliphatic structures and low amounts of condensed aromatics (Chin et al, 1997). This ratio is also inversely related to the degree of aromaticity, particle size, molecular weight and acidity (Uyguner et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Ultraviolet (UV) absorption spectrophotometer is generally used to study various properties of the DOC, such as its aromaticity, hydrophobic content, and biodegradability [2,[10][11][12] because DOM have constitute such type of components which have capacity to absorb the ultraviolet light for example unsaturated aliphatic bonds and benzenoid type components [13,14]. Specific absorbance at different specific wavelengths has been used to measure the aromaticity, hydrophobic content, apparent molecular weight and size, and biodegradability [15][16][17][18].UV-absorbance is good surrogate the concentration of DOM specifically concentration of aromaticity in DOM at 254 nm absorbance [13,18].…”
Section: Introductionmentioning
confidence: 99%
“…A possible sink is the reaction with organic matter, which is well known from water disinfection (e.g. Gallard and von Gunten, 2002;Uyguner et al, 2004). Voudrias et al (1985) report the reaction of phenolic compounds like phenol, catechol, and guaiacol with free chlorine by drinking water treatment processes and the formation of chlorinated aromatic compounds.…”
Section: Introductionmentioning
confidence: 99%
“…They suggested that these high values could result from the interaction of Cl ·− 2 with carboxylic acid functional groups of humic acids. THM formation from the reaction of molecular chlorine with humic substances was measured by Uyguner et al (2004) in water-treatment processes. Schöler and Thiemann (2005) report the natural formation of THM in the marine and terrestrial environment.…”
Section: Introductionmentioning
confidence: 99%